KECENDERUNGAN PENOKOHAN DALAM NOVEL BUMI CINTA KARYA HABIBURRAHMAN EL SHIRAZY - Yunisa Oktavia (Universitas Putera Batam, 2015)
Novel as a kind of literary that widely discussed by the public, especially for certain people who care and love towards literature. Novel can not be separated from the elements, they are intrinsic and extrinsic elements. Intrinsic elements as building of novel which covering the characterizations, themes and message,storyline, background, style, and viewpoints. Talking about the intrinsic elements of the novel, especially regarding the characterizations of the important element in literature. Characterizations belong to the naming issue, characterization, physical state, mental state, and the character. Eventually, the characterizations become a combination of character and disposition. This journal aims to describe the tendency of the characterizations contained in the novel Bumi Cintaby Habiburrahman El Shirazy. Characters and the physical state of the characters in the novel Bumi Cinta by Habiburrahman El Shirazy described and developed analytic and dramatic. Analytically, namely the direct author elaborated on the personality or characters, the author mentions that the figure pertinacious, stubborn, loving, and so on. While dramatic, the draftsman is not dispositive told directly by selecting names of characters, through physical depiction and through dialogue. Based on the data analysis and discussion of the conclusions of this study, it can be described as follows. First, the character Ayyas more highlighted in the novel Bumi Cinta by Habiburrahman El Shirazy. Second, the physical state Ayyas less portrayed as the main character in the novel Bumi Cinta by Habiburrahman El Shirazy so the physical of Ayyasis not handsome and ugly. Third, the supporting cast of characters in the novel Bumi Cintaby Habiburrahman El Shirazy can help to clarify the character of protagonist character. Fourth, the physical state of the novel Bumi Cinta by Habiburrahman El Shirazy is highlighted so that researcher can determines the physical state of the supporting cast as a whole.